2021
DOI: 10.3390/en14185797
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Auto-Ignition and Structure-Reactivity Trends of C2–C4 1-Alkenes

Abstract: Ignition delay times of small alkenes are a valuable constraint for the refinement of the core kinetic mechanism of hydrocarbons used in representing combustion properties of real fuels. Moreover, the chemical reactivity comparison of those small alkenes provides a reference in object-oriented fuel design and logical combustion utilization. In this study, the ignition delay times of C2–C4 alkenes (ethylene, propene and 1-butene) were measured behind reflected shock waves first, with a fixed oxygen concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The results indicated that the ignition delay time was reduced with an increase in the temperature, pressure, and mole fraction of kerosene, as well as with a decrease in the equivalence ratio. Sun et al [20] analyzed the combustion characteristics of small alkenes based on a sensitivity method and compared with the measured data of the ignition delay time. The established chemical reaction mechanism can be integrated with the fluid flow and heat transfer simulation in CFD software.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the ignition delay time was reduced with an increase in the temperature, pressure, and mole fraction of kerosene, as well as with a decrease in the equivalence ratio. Sun et al [20] analyzed the combustion characteristics of small alkenes based on a sensitivity method and compared with the measured data of the ignition delay time. The established chemical reaction mechanism can be integrated with the fluid flow and heat transfer simulation in CFD software.…”
Section: Introductionmentioning
confidence: 99%